2023
DOI: 10.1136/jcp-2022-208580
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of immediate prevalence of cervical precancers and cancers with HPV genotype and age in women with ASC-US/hrHPV+: a retrospective analysis of 2292 cases

Abstract: AimsTo stratify the risk of cervical precancers (high-grade squamous intraepithelial lesion (HSIL) and adenocarcinoma in situ (AIS)) and cancers (squamous cell carcinoma (SCC) and adenocarcinoma) based on distinct high-risk human papillomavirus (hrHPV) genotypes as well as age groups among women with atypical squamous cells of undetermined significance (ASC-US) and hrHPV+results.MethodsIn total, 2292 cases of ASC-US/hrHPV+ with immediate follow-up biopsy results were included in the study for prevalence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Our previous study showed that in the NILM/hrHPV‐positive population, the older patient group exhibited a lower risk of cervical precancer but a higher risk of cancer 21 . Similarly, in ASC‐US/hrHPV‐positive women, the prevalence of cervical SCC is significantly higher in older women than in younger women 22 . In the current study, 25–39 age years group showed a significantly higher prevalence of CIN1 ( p = .032).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our previous study showed that in the NILM/hrHPV‐positive population, the older patient group exhibited a lower risk of cervical precancer but a higher risk of cancer 21 . Similarly, in ASC‐US/hrHPV‐positive women, the prevalence of cervical SCC is significantly higher in older women than in younger women 22 . In the current study, 25–39 age years group showed a significantly higher prevalence of CIN1 ( p = .032).…”
Section: Discussionsupporting
confidence: 52%
“…21 Similarly, in ASC-US/hrHPV-positive women, the prevalence of cervical SCC is significantly higher in older women than in younger women. 22 In the current study, 25-39 age years group showed a significantly higher prevalence of CIN1 ( p = .032). However, similar to the findings in a study by Rodríguez,23 This study has some limitations.…”
Section: Discussionsupporting
confidence: 45%
“…"Because the rate of pre-neoplastic disease is low (8), few studies of women over age 30 have the power to further stratify by age in order to better inform guidelines" (7)(8)(9)(10)(11) Women with all grades of "pathology-confirmed cervical intraepithelial neoplastic (CIN)" showed a reduction in HR-HPV identification with age, with the most pronounced decline seen for HPV 16 infection, according to a recent study from the ATHENA trial, that contained data on more than thirty five thousand women aged thirty and older. "In the HPV in Perimenopause (HIP) cohort of routinely screened women age 35-60 years, we observed a similar trend of decreasing correlation between HR-HPV detection and cervical abnormalities with increasing age" Our goal was to learn more about the relationship between agerelated aberrant cytology and either HPV and HR-HPV detection (12)(13)(14).…”
Section: Introductionmentioning
confidence: 85%
“…However, different genotypes of hrHPV carry different risks of developing high-grade lesions 15 . In our previous studies, we demonstrated the benefit of risk-stratifying patients with NILM and ASC-US cytology based on hrHPV genotype for optimizing patient management 16 , 17 . However, there is limited research on the association between ASC-H/HSIL cytology and hrHPV infection using Aptima assays, particularly on a large scale in China.…”
Section: Introductionmentioning
confidence: 99%